Identidad, reconocimiento y lenguaje - Ramos Lalupú, Segundo Leonardo (2020)
Human identity needs the social recognition that inevitably passes through language. Identity is one of the constitutive dimensions of our condition as human beings with moral capacity. Being aware of our own identity allows us to make sense of our life. The question Who am I? synthesizes what distinguishes us from other living beings, what defines us as such in space and time. Not being aware of our identity could lead us to an existential crisis, not knowing who we are, where we are or why we exist. Contemporary man delighted by materialistic consumerism seems to have stopped wondering about his own identity, about his own self, and does not seek to make sense of his life. Contemporary man is very concerned about the hedonistic enjoyment of his personal life. The human being is the holder of an identity that needs to be recognized by others. Language makes possible the recognition of our identities.